Multi-institution Evaluation of Adherence to Comprehensive Postoperative VTE Chemoprophylaxis - Yang, Anthony D. (Ann Surg, 2020)
OBJECTIVES: The aims of this study were to: (1) measure the rate of failure to provide defect-free postoperative venous thromboembolism (VTE) chemo-prophylaxis, (2) identify reasons for failure to provide defect-free VTE chemoprophylaxis, and (3) examine patient- and hospital-level factors associated with failure. SUMMARY BACKGROUND DATA: Current VTE quality measures are inadequate. VTE outcome measures are invalidated for interhospital comparison by surveillance bias. VTE process measures (e.g., SCIP-VTE-2) do not comprehensively capture failures throughout patients’ entire hospitalization. METHODS: We examined adherence to a novel VTE chemoprophylaxis process measure in patients who underwent colectomies over 18 months at 36 hospitals in a statewide surgical collaborative. This measure assessed comprehensive VTE chemoprophylaxis during each patient’s entire hospitalization, including reasons why chemoprophylaxis was not given. Associations of patient and hospital characteristics with measure failure were examined. Results: The SCIP-VTE-2 hospital-level quality measure identified failures of VTE chemoprophylaxis in 0% to 3% of patients. Conversely, the novel measure unmasked failure to provide defect-free chemoprophylaxis in 18% (736/4086) of colectomies. Reasons for failure included medication not ordered (30.4%), patient refusal (30.3%), incorrect dosage/frequency (8.2%), and patient off-unit (3.4%). Patients were less likely to fail the chemoprophylaxis process measure if treated at nonsafety net hospitals (OR 0.62, 95% CI 0.39–0.99, P = 0.045) or Magnet designated hospitals (OR 0.45, 95% CI 0.29–0.71, P = 0.001). CONCLUSIONS: In contrast to SCIP-VTE-2, our novel quality measure unmasked VTE chemoprophylaxis failures in 18% of colectomies. Most failures were due to patient refusals or ordering errors. Hospitals should focus improvement efforts on ensuring patients receive VTE prophylaxis throughout their entire hospitalization.